2007
DOI: 10.1111/j.1464-5491.2007.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Length of gestation and gender are associated with HLA genotypes at risk for Type 1 diabetes (Italian DIABFIN 3)

Abstract: Length of gestation is inversely correlated with HLA risk categories for T1D. The higher the HLA risk for T1D, the shorter the gestational age, especially in male neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
(26 reference statements)
2
13
0
Order By: Relevance
“… and Locatelli et al . who did not find any significant associations between a high birth weight and HLA haplotypes conferring increased risk for T1D. Our results also agree with the outcome of the recent study by Sterner et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… and Locatelli et al . who did not find any significant associations between a high birth weight and HLA haplotypes conferring increased risk for T1D. Our results also agree with the outcome of the recent study by Sterner et al .…”
Section: Discussionsupporting
confidence: 93%
“…There have been also other studies looking for possible associations between HLA‐risk group and birth weight . Järvinen et al .…”
Section: Discussionmentioning
confidence: 99%
“…This may be genetically determined, but influence from other factors cannot be ruled out, such as length of pregnancy for which shorter length predisposes slightly to T1D (50, 51), and birth by caesarean section which increases the T1D risk by 23% (52). It is an attractive idea, but unknown whether low islet mass, which might be more stressful for the individual beta cell, predisposes to T1D.…”
Section: The Activity Of the Beta Cellsmentioning
confidence: 99%
“…In T1D, two studies have found a slightly shorter length of pregnancy in mothers of boys who later develop the disease (143, 144). Also, higher age of the mother (143) and higher birth weight predispose for T1D with an increased risk of 6–10% (145).…”
Section: Other Factors Related To Development Of T1d That Are Difficumentioning
confidence: 99%
“…Factors which have been suggested as having an association with an altered risk of developing T1D during foetal development are preeclampsia (Jones et al 1998), maternal age, birth weight and parity (Dahlquist et al 1999), gestational length (Locatelli et al 2007), maternal diabetes and maternal smoking (Marshall et al 2004) and sex of the child (Svensson et al 2005). It has also been suggested that ethnicity can be a risk factor, with a higher incidence in those of European descent (Borchers et al 2010) which is even further increased in those of Swedish descent (Dahlquist et al 1996;Hjern and Söderström 2008).…”
Section: Potential Confoundersmentioning
confidence: 99%